2021
DOI: 10.3390/ani11072072
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multimodal Role of Yucca schidigera Extract in Protection against Chronic Ammonia Exposure Targeting: Growth, Metabolic, Stress and Inflammatory Responses in Nile Tilapia (Oreochromis niloticus L.)

Abstract: Ammonia is a critical hazardous nitrogen metabolic product in aquaculture. Despite trials for its control, ammonia intoxication remains one of the most critical issues to overcome. In this study, we explored the modulatory effect and potential mechanism by which Yucca schidigera extract (YSE) can ameliorate ammonia intoxication-induced adverse effects on tilapia health and metabolism. A total number of 120 Nile tilapia were evenly assigned into four groups with three replicates each. The first group served as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…As ammonia has high affinity for blood hemoglobin, it displaces oxygen and influences some hematological properties [ 35 ]. Hematological properties are significant indicators to assess fish health status after exposed to different environmental stresses and chemical toxicity [ 36 , 37 , 38 , 39 ]. Ammonia enters the fish circulatory system and causes metabolic disturbances and fatal responses, such as oxidative stress, immune response and genetic expression [ 40 ].…”
Section: Hematological Parametersmentioning
confidence: 99%
“…As ammonia has high affinity for blood hemoglobin, it displaces oxygen and influences some hematological properties [ 35 ]. Hematological properties are significant indicators to assess fish health status after exposed to different environmental stresses and chemical toxicity [ 36 , 37 , 38 , 39 ]. Ammonia enters the fish circulatory system and causes metabolic disturbances and fatal responses, such as oxidative stress, immune response and genetic expression [ 40 ].…”
Section: Hematological Parametersmentioning
confidence: 99%
“…It has been suggested that lower growth rate at high stocking densities may be attributed to disturbed physiological activities of fish in relation to social stress and water quality deterioration. The lower water dissolved oxygen and higher ammonia levels explains the inferior growth and feed efficiency in the HD treatments, as they are two important factors in aquaculture productivity (Abdel‐Tawwab et al, 2019; Elbialy et al, 2021). Application of Artemisia in the fish diet created no beneficial effects on the fish performance at high stocking density, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that decrease in the blood WBC counts and lymphocyte percentage, and increase in neutrophil percentage are haematological responses to stress in fish (Elbialy et al, 2021; Zebral et al, 2015). Decreased WBC counts due to stress may compromise the ability of fish to cope with pathogens and other stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, of the 80% nitrogen component from the secretion, 90% is ammonia and 10% is uric acid (Ebeling et al 2006). Ammonia is toxic for aquatic organisms as it reduces dissolved oxygen and generates unwanted changes in the aquatic ecosystem (Elbialy et al 2021). Ammonia is especially toxic for fish culture at a concentration of >1.5 mg N/l.…”
Section: Discussionmentioning
confidence: 99%